Leagility in fashion supply chains: the potential of integration for managing complexity. (2nd August 2019) - Mahmood, Shahriare; Kropsu-Vehkaperä, Hanna; Kess, Pekka
Offshore manufacturing and outsourcing trend in recent days in fashion industry complicates their supply chain (SC). This study focuses to this perplexity and assesses the potentiality of leagility to achieve required competitiveness in such circumstances. The nature of the fashion supply chain is recapitulated and the aspect of leagility is observed within existing literature and through case studies. The tendency of global sourcing, e.g., quick supply of manufacture economically obliges them to rethink the SC strategy and leagility is beneficent in this context in absorbing the turbulence. This research provides a direction to the retailers unsure about the apt strategy by demonstrating the relevance of leagility in fashion SC. It also builds the base for further deeper study for implement the concept in different part of manufacturing chain.